2019
DOI: 10.1134/s1063772919110039
|View full text |Cite
|
Sign up to set email alerts
|

Search for Fast Radio Bursts in the Direction of the Galaxies M31 and M33

Abstract: The results of a search for individual fast radio bursts with the Large Phased Array of the Lebedev Physical Institute at 111 MHz during July 2012 through August 2018 are presented. The signals were distinguished by convolving the data with a template with a fixed form, followed by convolution with test dispersion measures. Areas of sky containing the galaxies M31 and M33 were chosen for the search.Three radio bursts were detected in the vicinity of M33, five in the vicinity of M31, and one in a region offset … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…According to FRBCAT, there is a significant gap between ∼ 35 ms and ∼ 300 ms in pulse width. However, we notice that the measurements with pulse width larger than ∼ 300 ms all come from one radio facility, i.e., the radio telescope BSA LPI of the Pushchino Radio Astronomy Observatory, in which the time interval between samples is 100 ms (Fedorova & Rodin 2019). Considering that there may exist some observational bias effects in these data, we only include the pulses with a width shorter than ∼ 35 ms (80 non-repeaters).…”
Section: Frb Observation Datamentioning
confidence: 99%
“…According to FRBCAT, there is a significant gap between ∼ 35 ms and ∼ 300 ms in pulse width. However, we notice that the measurements with pulse width larger than ∼ 300 ms all come from one radio facility, i.e., the radio telescope BSA LPI of the Pushchino Radio Astronomy Observatory, in which the time interval between samples is 100 ms (Fedorova & Rodin 2019). Considering that there may exist some observational bias effects in these data, we only include the pulses with a width shorter than ∼ 35 ms (80 non-repeaters).…”
Section: Frb Observation Datamentioning
confidence: 99%
“…We note that detection of 9 plus 51 bursts at 111 MHz using the Large Phased Array of the Pushchino Radio Astronomy Observatory has been claimed by [123,124]. However, the observational setup of their system (a coarse frequency resolution of 78 kHz over a tiny observation bandwidth of 2.5 MHz, and a sampling time not faster than 12.5 ms) required the use of a template matching approach in order to see the bursts.…”
Section: Large Phased Arraymentioning
confidence: 90%
“…In the work of Fedorova and Rodin [11] it was shown that the average rate of registration of bursts by the LPA LPI radio telescope at a frequency of 111 MHz is ∼ 2000 pulses/year.…”
Section: Catalog "Prao Frbs At 111 Mhz"mentioning
confidence: 99%
“…Nine more single pulses were detected, including one repeating pulse. All the events showed no apparent concentration towards the centers of the M31 and M33 galaxies [11]. In order to start making meaningful reliable conclusions about the properties of new pulses, it was necessary to increase their statistics to several dozen, so a search was started for the entire available area of the sky.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation